A study on soil moisture retention and consistency limits as affected by soil amendments - SHIZA DOMINIC; Sreedevi V. P; Subini S. Nair; Er. Alexander Seth (guide) (Tavanur 2002 Kelappaji College of Agricultural Engineering and Technology)
A study on soil moisture retention and consistency limits as affected by soil amendments
A study on soil moisture retention and consistency limits as affected by soil amendments